IMPLEMENTATION OF BABY SCALES WITH ESP32 MICROCONTROLLER BASED ON ANDROID - Sudaryanto, Eko; Watiningsih, Tri; Panorama Filardi, Ananda; Darmawan, Isra' Nuur (Journal of Electronic and Electrical Power Applications, 2024)
Prevention and monitoring of infant growth and development through weighing activities is the easiest thing to do. After weighing, recording is usually done manually, if there is an error or forgetfulness it becomes a problem in the future. For this reason, a digital weight measuring tool is needed that is integrated with a smartphone for automatic recording and is recorded periodically. A more practical weight measuring prototype with a level of accuracy and a database that is recorded without any errors. Of course with various features that can facilitate accessibility, ease of use, complex integration and others. Based on the tools that have been made and the research that has been done, the author can conclude that, a digital baby scale has been made using a loadcell sensor component, HX711 module, ESP32, LCD 16x2 I2C is able to work very well in reading the load. In testing the loadcell sensor which functions to read the weight value by weighing a 500 gram pendulum, it produces an average value of 0.2% with an accuracy level of 99.8%. Comparison of digital scales with research scales was carried out by testing the weight of 5 pendulums with each weighing 50 grams, 100 grams, 200 grams, 500 grams, 1000 grams, resulting in an average error value of 0.165%, which means the accuracy value is 99.835%.